Penggunaan Naskah Kuno dan Arsip dalam Historiografi Indonesia: Suatu Tinjauan Kritis - Heru Mulyanto (Perpustakaan Nasional RI, 2023)
Archives and ancient manuscripts are actually categorized in the primary historical sources that will determine the success of Indonesian historiography products. However, this success faced new challenges with a change in perspective from Indonesia-centric which was inclined to colonial-centric because of the dominant use of colonial archives from Indonesian manuscripts. The history of Indonesia, which should have been written with original Indonesian sources, is now more dominantly written with colonial sources. This article aims to criticize which is more dominant between local archives and manuscripts in their use to reconstructing Indonesian history. This paper also aims to prove Bambang Purwanto’s theory regarding the disorientation of Indonesian Historiography which turned away from local manuscripts oral sources. Descriptive-qualitative method is used here, to analyze influential historiographical works in Indonesia in making use of local manuscripts and archives. The results of the analysis show that historians face more challenges in using local manuscripts than colonial archives. Colonial archives are considered more straightforward and comprehensive in proving historical witness, while ancient manuscripts tend to have fictional elements that must be separated from the factual elements in them.